2021
DOI: 10.1371/journal.pntd.0009650
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Leishmaniasis in pregnancy and vertical transmission: A systematic literature review on the therapeutic orphans

Abstract: Background Reports on the occurrence and outcome of Visceral Leishmaniasis (VL) in pregnant women is rare in published literature. The occurrence of VL in pregnancy is not systematically captured and cases are rarely followed-up to detect consequences of infection and treatment on the mother and foetus. Methods A review of all published literature was undertaken to identify cases of VL infections among pregnant women by searching the following database: Ovid MEDLINE; Ovid Embase; Cochrane Database of Systema… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…Hence, this formulation can be an alternative drug used for the treatment of leishmaniasis. These results are consistent with the previous report that suggested liposomal amphotericin B was the preferred therapy choice for the management of VL in pregnant women ( Mishra et al, 2007 ; Solomon et al, 2007 ; Dahal et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…Hence, this formulation can be an alternative drug used for the treatment of leishmaniasis. These results are consistent with the previous report that suggested liposomal amphotericin B was the preferred therapy choice for the management of VL in pregnant women ( Mishra et al, 2007 ; Solomon et al, 2007 ; Dahal et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…While amphotericin B, particularly its liposomal derivative (L-AMB), is considered safe and effective in the treatment of VL in pregnancy, and has been widely used for cutaneous and mucosal leishmaniasis in South America, this is the first published report of its use in CL in a pregnant patient [ 6 , 13 ]. There is no standard dosage regimen of L-AMB for either VL in pregnancy or MCL in any host.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models have demonstrated that vertical transmission can occur in both VL and CL/MCL 18 . Miscarriages, preterm births, small‐for‐gestational‐age infants, and fetal loss/stillbirths have been described in both VL and CL/MCL 15,19,20 …”
Section: Introductionmentioning
confidence: 99%
“…18 Miscarriages, preterm births, small-for-gestational-age infants, and fetal loss/stillbirths have been described in both VL and CL/MCL. 15,19,20 Although various treatment options exist for MCL, pregnancy significantly limits the number of safe agents available.…”
mentioning
confidence: 99%